Mainstreaming Citizen Engagement in Public Financial Management for Better Results - Kumagai, Saki; Bandyopadhyay, Sruti; Grandvoinnet, Helene (World Bank, Washington, DC, 2020)
Public financial management (PFM) is fundamental for effective resource management and the backbone for effective and efficient public service delivery. Citizen engagement (CE) in the PFM cycle contributes to achieving better development outcomes by mobilizing citizens in the PFM process, supporting more inclusive budget processes, and establishing pro-poor fiscal policies. Based on a desk review, this note is intended to provide a menu of CE entry points in the PFM cycle and serve as a reference guide to support World Bank task teams. It indicates that CE in PFM needs to move beyond transparency to achieve development objectives; budget literacy for inclusive CE is critical for both government and citizens; and two polarized types of engagement in PFM — engagement with the general public and engagement with small, selected, and specialized groups for in-depth feedback — are complementary to each other in achieving effective budget outcomes.